2014
DOI: 10.1080/09593330.2014.930514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an aerobic treatment for olive mill wastewater detoxification

Abstract: Olive mill wastewater (OMWW) is a by-product of the olive oil extraction industry. Its dumping creates severe environmental problems in the Mediterranean countries. The phytoxicity of OMWW is due to the phenolic substances and is evaluated through a genotoxicity method. An aerobic treatment of OMWW was conducted during 45 days. Different concentrations of raw and treated OMWW were tested using the Vicia faba micronuclei test. Results showed that raw OMWW induced significant micronuclei formation at 10% of OMWW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…However, there is a limited and contradictory evidence for such a protective role on DNA damage. Recently, oleuropein was demonstrated to be genotoxic by the micronucleus test . Instead, we demonstrated that oleuropein may prevent the ROS‐induced DNA damage in a high concentration range.…”
Section: Discussionmentioning
confidence: 70%
“…However, there is a limited and contradictory evidence for such a protective role on DNA damage. Recently, oleuropein was demonstrated to be genotoxic by the micronucleus test . Instead, we demonstrated that oleuropein may prevent the ROS‐induced DNA damage in a high concentration range.…”
Section: Discussionmentioning
confidence: 70%
“…Toxicity evaluation, especially acute toxicity, has already been adopted for wastewater management in many countries routinely (Power and Boumphrey, 2004), where various test organisms can be used to characterize the acute toxicity of wastewater (Manenti et al, 2015;Santos et al, 2014;El Hajjouji et al, 2014). Acute toxicity evaluation for municipal wastewater has also been conducted in recent years with aquatic organisms, such as luminous bacteria, algae and fish (Mendonca et al, 2013;Ma et al, 2013Ma et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…C p specific heat of water (kJ/kg°C) CV calorific value of fuel (kJ/kg) FC mass of fuel consumed (kg) H 1 sensible heat utilisation (kJ) H 2 latent heat utilisation (kJ) T 1 initial Temperature of water (°C) T 2 final temperature of water (°C) w amount of water evaporated (kg) W 1 initial weight of water (kg) W f final weight of water (kg) η th thermal efficiency…”
Section: Nomenclaturementioning
confidence: 99%
“…The thermal efficiency and the power rating of the developed cookstove were estimated using Equations (1) and (2). The thermal efficiency of the cookstove was estimated as 36.38% with a thermal power rating of about 5.0 kW.…”
Section: Thermal Performancementioning
confidence: 99%
See 1 more Smart Citation